Optimization of community-based mental health services: a systematic review - Almi, Ahmad Anas; Abdul Khaiyom, Jamilah Hanum (Emerald Publishing Limited, 2020)
Purpose – This paper aims to review the literature of community-based mental health services (CMHS) optimization in Malaysia that focus on the aspects of perceived challenges or barriers and facilitating factors for community-based mental health centre (CMHC).